2017
DOI: 10.3126/jpn.v7i2.18031
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous leishmaniasis

Abstract: Leishmaniasis is considered to be zoonotic disease, caused by a protozoan parasite of the genus Leishmania, and transmitted by a bite of infected female sandfly. Primary cutaneous leishmaniasis is not common disease in Nepal, however, there were cases reported from Terai region of Nepal. The patients with cutaneous leishmaniasis present with a papule or nodule at the site of inoculation, followed by formation of crusts. Differential diagnoses of cutaneous leishmaniasis include variety of skin diseases, inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…In the present study, the disease was more common in males with male to female ra o of 1.7:1. This fi nding is similar to studies done by Aara N et al 9 and Srivastava et al 13 In contrast, other authors have found a higher incidence of disease in females. 11,12 In Nepal, females are mostly involved in household works and males are involved in outdoor works.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, the disease was more common in males with male to female ra o of 1.7:1. This fi nding is similar to studies done by Aara N et al 9 and Srivastava et al 13 In contrast, other authors have found a higher incidence of disease in females. 11,12 In Nepal, females are mostly involved in household works and males are involved in outdoor works.…”
Section: Discussionsupporting
confidence: 92%
“…Most of our pa ents had single lesion which is similar to the fi nding of Aara N et al 9 and Galgamuwa LS et al 14 In our study, lesions were more common in face. Other authors have also reported similar fi ndings.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations